2009
DOI: 10.1111/j.1556-4029.2008.00975.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Photodegradation of Crystal Violet upon Light Exposure by Mass Spectrometric and Spectroscopic Methods

Abstract: Crystal violet is a very common dye in ballpoint ink. Recent research suggests that the degradation of triarylmethane dyes gives an indication of the age of a ballpoint pen entry on a document. The main problem for the quantitative evaluation of the degradation is that it is highly dependent on the exposure to light. Moreover additional factors, such as additives and substrate play an important role in this process. The aim of this work is to compare the degradation pathways of the pure dye in water and ethano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
66
0
5

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(75 citation statements)
references
References 16 publications
4
66
0
5
Order By: Relevance
“…The graph confirms that the molecular ion RPA values of the triphenylmethane cationic dye BV3 (RPA 372 ) decreased in correlation to nominal laser irradiance, while degradation products were formed (i.e., increasing values of RPA 358 and RPA 344 ). Similar observations were previously reported in the literature [19,20] and demonstrate that dependence between laser irradiance and degradation of cationic dyes is a consequence that have to be considered if LDI-MS is used to discriminate inks. No information of this type was yet proposed for negative ions.…”
Section: Optimization Of the Methodssupporting
confidence: 86%
See 1 more Smart Citation
“…The graph confirms that the molecular ion RPA values of the triphenylmethane cationic dye BV3 (RPA 372 ) decreased in correlation to nominal laser irradiance, while degradation products were formed (i.e., increasing values of RPA 358 and RPA 344 ). Similar observations were previously reported in the literature [19,20] and demonstrate that dependence between laser irradiance and degradation of cationic dyes is a consequence that have to be considered if LDI-MS is used to discriminate inks. No information of this type was yet proposed for negative ions.…”
Section: Optimization Of the Methodssupporting
confidence: 86%
“…This ensures high discrimination power considering that combinations of organic dyes and inorganic pigments are highly variables in ink formulations [15]. Secondary ion mass spectrometry (SIMS) [4], field desorption (FD) [5], electrospray ionization (ESI) [7], laser desorption/ionization (LDI) [6,12,[16][17][18][19][20], matrix-assisted laser desorption/ionization (MALDI) [19,21], direct analysis in real time (DART) [8] and desorption electrospray ionization (DESI) [22,23] were proposed for ballpoint inks examination. In addition to classical methods, mass spectrometry may yield information on the structure of the analyzed molecules (i.e., mass or/and fragmentation pattern).…”
Section: Introductionmentioning
confidence: 99%
“…Here, the photoreduction of the excited dye cation is achieved by the addition of an electron to dye photoexcited states or by photochemical hydrogenation of a dye [9,13].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, materials of paper documents can also be very different in their structure and chemical composition. Therefore, it is quite important to study in detail the aging process of dyes taking into account all aforementioned factors [13].…”
Section: Introductionmentioning
confidence: 99%
“…It was based on the changes in the extractability of the ink supposedly caused by the hardening of the resins [10,[21][22][23][24]. The use of this technique in caseworks was reported in the literature [18,25], but it was followed by a vigorous controversy among the scientific community about the limitations of this approach [5,[26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42]. Several researchers tried reproducing the results obtained in previous studies and reported the methods to be unreliable [28,[34][35][36], while other scientists debated about the necessity for inter-laboratory validation before their use in casework [4,27,[31][32][33]38,41].…”
Section: Introductionmentioning
confidence: 98%